2020
DOI: 10.1055/s-0040-1713001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Treatment Courses, and Distribution of Cytomegalovirus Genotypes among Thrombocytopenia Patients Aged Younger than 12 Months

Abstract: Objective The aims of this study were to evaluate the clinical characteristics, laboratory data, and treatment of the cytomegalovirus (CMV)-associated thrombocytopenia in infants aged younger than 12 months and to investigate the possible relationship between genotypes of glycoprotein B (gB) and glycoprotein H (gH) and CMV-associated thrombocytopenia. Study Design Infants with positive identification of cytomegalovirus (CMV) and thrombocytopenia, being treated at Hubei Maternal and Child Health Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 25 publications
(39 reference statements)
0
15
0
1
Order By: Relevance
“…Our previous studies also confirmed that the gB1 genotype had more virulence in infants with symptomatic CMV disease. 3,4 But interestingly, in asymptomatic infected infants, gB1 was also the dominant genotype, and its genotype distribution was not significantly different from that of CMV-associated thrombocytopenia infants.…”
Section: Genotype Associationmentioning
confidence: 85%
See 2 more Smart Citations
“…Our previous studies also confirmed that the gB1 genotype had more virulence in infants with symptomatic CMV disease. 3,4 But interestingly, in asymptomatic infected infants, gB1 was also the dominant genotype, and its genotype distribution was not significantly different from that of CMV-associated thrombocytopenia infants.…”
Section: Genotype Associationmentioning
confidence: 85%
“…Our previous studies also confirmed that the gB1 genotype had more virulence in infants with symptomatic CMV disease. 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the major infectious causes that induce thrombocytopenia. Minimal data are available on the association between CMV infection and thrombocytopenia during early infancy [ 2 ]. The most common form of CMV infection is asymptomatic or benign in immunocompetent children [ 3 ], but CMV infections occurring during the neonatal period can be serious or even fatal.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several envelope glycoproteins, encoded by UL55, UL73, and UL75, including glycoprotein B (gB), glycoprotein N (gN), and glycoprotein H (gH), respectively, have been evaluated in clinical CMV iso-lates because of their influence on tissue tropism and virulence. [2][3][4] The UL144 polymorphisms are concentrated in the 5′ end of the gene, especially in cysteine-rich domain 1 (CRD1), that may bind the B-and T-lymphocyte attenuator proteins. This domain's activity may vary among polymorphisms, leading to a range of clinical symptoms and prognoses.…”
Section: Introductionmentioning
confidence: 99%